Untying a Protein Knot by Circular Permutation. Issue 4 (15th February 2019) - Chuang, Ya-Chu; Hu, I-Chen; Lyu, Ping-Chiang; Hsu, Shang-Te Danny
Abstract: Topologically knotted proteins are tantalizing examples of how polypeptide chains can explore complex free energy landscapes to efficiently attain defined knotted conformations. The evolution trails of protein knots, however, remain elusive. We used circular permutation to change an evolutionally conserved topologically knotted SPOUT RNA methyltransferase into an unknotted form. The unknotted variant adopted the same three-dimensional structure and oligomeric state as its knotted parent, but its folding stability was markedly reduced with accelerated folding kinetics and its ligand binding was abrogated. Our findings support the hypothesis that the universally conserved knotted topology of the SPOUT superfamily evolved from unknotted forms through circular permutation under selection pressure for folding robustness and, more importantly, for functional requirements associated with the knotted structural element. Graphical Abstract: Unlabelled Image Highlights: Circular permutation is introduced to untie a topologically knotted SPOUT RNA methyltransferase while maintaining its overall structure. The unknotted circular permutant may resemble the ancestor of the universally conserved SPOUT superfamily. The knotted structural element may evolve through the selection pressure for cofactor binding and folding stability.